Balancing Optimism and Realism: Indonesia’s Urban Youth’s Political Engagement in the 2024 General Elections - Sugiyono, Paulus Bagus; Ajisukmo, Clara R.P.; Rosario, Teresa Metta; Soge, Yeremias Siane Ikang; Wijoyo, Vinsenso Valdis Amor (Universitas Negeri Malang, 2024)
The discourse around youth political participation often seems pejorative. Many earlier studies continue to emphasise youth political apathy, a notion that has long been debunked. Others reduce urban youth’s political engagement to merely digital activism, largely due to recent information and technological advancements. However, this research presents a more nuanced view, arguing that the current political engagement of urban youth is characterised by a balance of optimism and realism. An online survey of 205 Indonesian youths from various cities was conducted to gauge their perspectives on political participation, including their views on the 2024 general elections. They were asked to examine some sets of statements as descriptions and explanations of their political stances. The results suggest that urban youth in Indonesia are keen to be politically active, including in the 2024 general elections. They stay informed, regularly following political news and candidate debates, signalling hope for a healthier democracy. However, they remain pragmatic, recognising the flaws in politics, such as corruption, inefficient administration, and political dynasties, which they view as the “dirty side” of politics. This dual perspective reflects a more complex political stance, where youth are motivated to participate yet grounded in the reality of the political system’s imperfections.